Effects of design sensitivity schemes for incorporating loading uncertainty in robust topology optimization. Issue 2 (1st February 2023) - Wang, Dong
Abstract : The effects of different design sensitivity schemes for an appropriate incorporation of the loading position uncertainty into a gradient-based topology optimization procedure are explored intensively, so that the robust optimal design of a continuum structure can be efficiently performed over the prescribed uncertain region. Three compliance sensitivity schemes are tested and the distinctive strategy offering the most reliable and competitive material layout of the load-bearing components is obtained from comprehensive comparisons. Three benchmark examples are used to demonstrate the diverse configurations of the material layouts. The numerical results show that the scheme with the largest absolute design sensitivity can most adequately integrate the load uncertainties into the topology optimization algorithm to make the structural performance insensitive to, or have less degradation in the presence of perturbations in the loading points.